Are Malay small-scale agro-entrepreneurs ready to face future challenges? An analysis of attitudes towards work values - Tamam, Ezhar; Md. Sail, Rahim; Mohamed, Zainal Abidin; Abdullah, Amin Mahir; Hamzah, Mohammad Rezal; Yaakob, Zamree (Universiti Putra Malaysia Press, 2008)
A vital question receiving much attention in the revitalization of the agro-food sub sector in Malaysia concerns the readiness of Malay small-scale agro-entrepreneurs to compete in an increasingly competitive agriculture market. This study reports on the readiness of Malay small-scale commercial farmers in terms of attitude towards entrepreneurial work values. Seven hundred and eighty five Malay small-scale farm producers participated in the survey. A variation of attitudes towards performance, continuous improvement, quality, and innovation/risk-taking values were observed. Most of them had a positive rather than a very favorable attitude towards the four entrepreneurial work values. Hence, many are still vulnerable to compete in an emerging liberalized market. The results showed that the attitudes towards entrepreneurial work values significantly differed according to factor of participation in non-formal courses, participation in business networks, age, and level of education. Implications of the findings are discussed.